Indonesia Export, Import, and Demand for Domestic Commodities under Economics Liberalisation - Andi Irawan (Economic Journal of Emerging Markets, 2011)
The aim of this research is to identify the behaviour of export, import and domestic commodities demand in liberalization era both in the long run and the short run. This research applies the Vector Error Correction Model, Johansen Cointegration Test, Impulse Response Analysis and Granger Causality Test. The data range from 1993:01 to 2002:12. The result shows that in the long run the cross-price elasticity of imported non agricultural goods with respect to demand for domestically produced goods have lower magnitudes than own price elasticity of domestically produced goods. The demand elasticity of import commodities is elastic but that of domestic commodities is inelastic. Keywords: Import, Export, Economic Liberalization, Vector Error Correction Model